Exposure to ethnic discrimination in social media and symptoms of anxiety and depression among Hispanic emerging adults: Examining the moderating role of gender. Issue 3 (1st September 2020) - Cano, Miguel Ángel; Schwartz, Seth J.; MacKinnon, David P.; Keum, Brian T. H.; Prado, Guillermo; Marsiglia, Flavio F.; Salas‐Wright, Christopher P.; Cobb, Cory L.; Garcini, Luz M.; De La Rosa, Mario; Sánchez, Mariana; Rahman, Abir; et al.
Abstract: Method: Two hundred Hispanic emerging adults from Arizona ( n = 99) and Florida ( n = 101) completed a cross‐sectional survey, and data were analyzed using hierarchical multiple regression and moderation analyses. Results: Higher social media discrimination was associated with higher symptoms of depression and generalized anxiety. Moderation analyses indicated that higher social media discrimination was only associated with symptoms of depression and generalized anxiety among men, but not women. Conclusion: This is likely the first study on social media discrimination and mental health among emerging adults; thus, expanding this emerging field of research to a distinct developmental period.